Social Movement Learning and Social Innovation: Empathy, Agency, and the Design of Solutions to Unmet Social Needs. Issue 2 (May 2019) - Bennett, Elisabeth E.; McWhorter, Rochell R.
The Problem: Social innovation (SI) is integral to productive outcomes that resolve unmet social needs in various social movements throughout history, and it has become a movement of its own. SI provides a powerful place for social movement learning (SML) where solutions are often discovered through partnership of cross-sector affiliates who engage in creative work that often challenges the status quo in society. This learning is little understood let alone leveraged in the field of Human Resource Development (HRD). The Solution: The purpose of this article is to explore SI as a site of SML and illuminate design thinking as an underlying learning process for the SI movement with implications for HRD. SI is predicated on sincerely held social values and more specifically empathy for others, and these are embedded in design thinking, which is a technique that HRD professionals can add to the toolbox and use when partnering with affiliates in corporate social responsibility projects, designing innovation initiatives, and working for social organizations. This article argues that learning to empathize with people who are subjects of innovation is a fundamental learning outcome in the social movement, as is agency, or the belief that one can act to create change, such as developing feasible and workable solutions to unmet social needs. The Stakeholders: Stakeholders include HRD professionals, leaders and employers, social organizations and centers, and social movements and students in higher education that engage in SI projects that prepare them for working with innovation and to meet the social needs in society, whether home or abroad.